Correlation between Serum Uric Acid and HbA1c Levels in Patients with Type 2 Diabetes Mellitus - Rifan Nugraha; Nina Tristina; Miftanurachman Miftanurachman (Althea Medical Journal, 2018)
Background: Indonesia ranks fourth among countries with the highest number of diabetics. Increasing evidence suggests that hyperuricemia is an independent risk factor for impaired fasting glucose (IFG) and type 2 diabetes.  Some observational studies have identified elevated uric acid concentration as a risk factor for diabetes, while others have found an inverse relationship. The present study was conducted to discover the strength and the direction of the correlation. Methods: This study was an analytical cross-sectional study conducted from May to October 2014. The study subjects were 56 medical records of new outpatients diagnosed with T2DM in the Internal Medicine Polyclinic who underwent laboratory examination at the Clinical Pathology Unit of Dr. Hasan Sadikin General Hospital, January-December 2013. Result: The correlation between HbA1c and uric acid levels on the whole subject revealed a weak but significant negative correlation (r=-0.354, p=0.007). There was an insignificant negative correlation in male subjects (r=-0.405, p=0.120); in female subjects (r=-0.319, p=0.05), the correlation was a weak but insignificant negative correlation.Conclusions: There is a weak correlation between HbA1c and uric acid levels in patients with Diabetes Mellitus type 2.